On the timing of retreat of the Loch Lomond ('Younger Dryas') Readvance icefield in the SW Scottish Highlands and its wider significance. (1st September 2019) - Lowe, John; Matthews, Ian; Mayfield, Roseanna; Lincoln, Paul; Palmer, Adrian; Staff, Richard; Timms, Rhys
Abstract: It has long been assumed that the last glacier expansion in the Scottish Highlands, the Loch Lomond Readvance (LLR), resulted from a cold reversal that was broadly coeval with the 'Younger Dryas' episode. This view has recently been challenged, with the suggestion that glacier ice had disappeared from Rannoch Moor, one of the main ice accumulation centres in the SW Scottish Highlands, by as early as 12.5 ka, i.e. within the first half of the 'Younger Dryas'. Here we present new radiocarbon, tephrostratigraphical and pollen-stratigraphical evidence from one of the key sites on Rannoch Moor, the results of an experiment designed to test this hypothesis. Our results not only contradict that concept, but are fully compatible with other evidence from the SW Scottish Highlands that suggests that the LLR glaciers in this area continued to expand until towards the end of the 'Younger Dryas' period, and may have persisted in some places after the onset of the Holocene. We consider the possible reasons for this marked divergence in chronology, a matter that is crucial to resolve because the precise timing of the demise of the LLR glaciers has important palaeoclimatic and other implications. In the wider context, we also draw attention to problems with the general use of the term 'Younger Dryas' and why we regard the Greenland stratotype unit and term 'Greenland Stadial 1' (GS-1) a more secure stratigraphic comparator. Highlights: This paper is about one of the last major icefields to occupy the Scottish Highlands. Our new data suggest this icefield was an extensive ice body until ∼11, 500 years ago. These results run counter to recent publications advocating much earlier ice decay. The results have important palaeoclimatic and age-calibration implications. This study also exemplifies problems with the general use of the term 'Younger Dryas'.